Association between disease awareness and prognosis in patients with glioblastoma - Yanjiao Wu; Xiaoying Xue; Shuying Ji; Wenyan Wang; Lei Tian; Xuetao Han; Linlin Su; Junling Liu (Medicine, 2026)
This study aimed to evaluate whether disease awareness among Chinese patients with glioblastoma was associated with prognosis. This single-center, retrospective cohort study included consecutive patients diagnosed with glioblastoma between February 2009 and August 2020. Disease awareness was categorized as full awareness, midway awareness, awareness of lesser severity, and unawareness based on documented medical records and follow-up information. Overall survival (OS) and recurrence-free survival (RFS) were analyzed using Kaplan–Meier and Cox regression methods, with censoring applied for patients without death or recurrence events. Ninety-three patients were included. The median age was 53 years (interquartile range [IQR], 45–64), and 57.0% were male. The patients were classified according to disease awareness category: full awareness in 25.8%, midway awareness in 26.9%, awareness of lesser severity in 21.5%, and unawareness in 25.8%. After a median follow-up of 37.81 months, the median OS was 21.11 months (95% confidence interval [CI]: 19.30–32.98), and the median RFS was 24.99 months (95% CI: 16.01-not estimable). Disease awareness was not significantly associated with OS or RFS after adjustment for potential confounders, including treatments. Midway awareness showed a nonsignificant numerical pattern toward longer OS (hazard ratio, 0.631; 95% CI: 0.331–1.204; P = .163). Disease awareness level was not significantly associated with OS or RFS in this cohort. The numerically longer OS observed among patients with midway awareness should be interpreted as exploratory and hypothesis-generating and requires confirmation in larger prospective studies.